Analisis Profitabilitas Ditinjau Dari Aktivitas Bisnis Perusahaan (Studi kasus pada PT. Ekadharma International Tbk – EKAD yang Terdaftar di Bursa Efek Indonesia) - Septiansyah, Septiansyah; Munawar, Aang (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
In general, the purpose of the establishment of a company is to obtain maximum profit. Profitability is the ability of a company to earn a profit (profit) in a certain period. The profitability ratios measure the effectiveness of management based on return generated from sales and investments. The purpose of this analysis is to know the profitability analysis by using the company’s financial statements for five years ie the period 2012-2016 in companies engaged in the field of the chemical sub-sector. This analysis is taken because there is still a difference of analysis between analysis one with other analysis. This research is conducted by using financial ratio analysis method. By using the analysis of financial ratios, it can be seen that profitability ratios, activity, liquidity, and solvency of the company affect the company’s profitability, this can occur because of internal and external factors contained within a company. Then it can be concluded that profitability can affect the growth of the company.